PENGARUH TANGGUNGAN KELUARGA DAN DEDIKASI GURU TERHADAP PENAWARAN TENAGA KERJA GURU SMA SWASTA DI KOTA JAMBI - Kuswanto Kuswanto; Kesih Merdiyanti; Sahara Sahara (STKIP Persada Khatulistiwa Sintang, 2026)
Private high school teachers often face economic uncertainty and a maldistribution of workload, yet many persist and even volunteer to increase their teaching hours. This phenomenon indicates a complex interaction between household economic needs and intrinsic professional motivation in determining their work allocation decisions. This study aims to analyze the influence of the number of family members and the teacher's level of dedication on the supply of private high school teachers in Jambi City. Data were collected from 94 respondents through a closed-ended questionnaire in a quantitative survey design, and then analyzed statistically. The analysis results indicate that the size of family members is not a strong enough motivator to increase teachers' working hours. Conversely, a high level of dedication has been shown to significantly encourage teachers to allocate more time to teaching. However, simultaneously, the combination of family pressures and strong dedication has been shown to increase the willingness of teachers to offer their labor to schools. As a recommendation, school administrators are strongly encouraged to focus on creating a conducive work environment to maintain the dedication of educators. Furthermore, future researchers are advised to add other variables or employ a mixed methods research approach.